Target strength and school size assessment of scads using hydroacoustic - Hermawan, Maman (Fakulti Sains dan Teknologi, 2011)
The study has been conducted with two phases. The first phase involving laboratory experiment on fish target strength measurements of three commercially important pelagic fish species of the scads namely Round scad {Decapterus maruadsi), Ox-eye scad (Selar boops) and Yellow-banded scad {selaroides leptolepis). The second phase include both in situ side aspect target strength and fish schools estimation attracted around fish aggregating light. Fish physical characteristics such as total length, fork length, standard length, and weight were recorded in order to study relationship of TS to fish size. The samples sizes of Round scad, Ox-eye scad and Yellow-banded scad ranged from 11.40 to 20.50 cm, 10.0 to 20.7 cm and 7.0 to 15.6 cm (standard length), respectively.